PERBEDAAN SEGMENTASI DEMOGRAFIS BERDASARKAN PEMANFAATAN MEDIA SOSIAL DI KELURAHAN PLAJU ULU PALEMBANG - Puspasari, Mardiana; Septadiyanto (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2020)
The formulation of the problem in this research was to find out whether there was any difference of demographic segmentation based on social media utilization in Kelurahan Plaju Ulu Palembang. The purpose of this research was to know the difference of demographic segmentation based on social media utilization in Kelurahan Plaju Ulu Palembang. The type of the study used comparative research. The variable that were compared in this research were demographic segmentation based on social media utilization. The population in this study was the community in Kelurahan Plaju Ulu Palembang consisting of Rw 01, Rw 05, Rw 09 and Rw 16 that was 1169 as the sample with Cluster Sampling technique. Primary data was needed as the basis analysis, while the data collection technique was a questionnaire. The analysis technique used Chi Square. The result of the study through Kai Squares test (X2) showed that there was the difference of demographic segmentation based on social media utilization in Kelurahan Plaju Ulu Palembang, but only included: (1) job difference based on frequency of use, (2) age difference based on frequency and usage user, (3) and the difference in revenue based on usage user. From these results it was also known that there ware no difference, which included: (1) gender based on frequency, utilization and type of social media, (2) occupation based on utilization and type of social media, (3) age by type of social media, (4) income based on frequency and type of social media, (5) religion based on frequency, utilization and type of social media.